2010
DOI: 10.1248/bpb.33.168
|View full text |Cite
|
Sign up to set email alerts
|

The Resorcylic Acid Lactone Hypothemycin Selectively Inhibits the Mitogen-Activated Protein Kinase Kinase-Extracellular Signal-Regulated Kinase Pathway in Cells

Abstract: Resorcylic acid lactones (RALs) constitute a family of polyketide mycotoxins with a variety of biological activities.1) Representative examples are the heat shock protein 90 inhibitor radicicol and the estrogen agonist zearalenone. Hypothemycin ( Fig. 1), a RAL containing a cis-enone moiety that initially did not reveal any particularly interesting activity, was later shown to inhibit ras-transformation and T cell activation. [2][3][4] Hypothemycin and other closely related cis-enone RALs gained attention as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Four new compounds (2,(4)(5)(6), two new natural products (1,3), and six known compounds (7)(8)(9)(10)(11)(12) were isolated from the mycelial solid culture of an endophytic fungus P. ochrochloron SWUKD4.1850 from the medicinal plant K. angustifolia after successive separation steps using various column chromatography (CC) methods (▶ Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four new compounds (2,(4)(5)(6), two new natural products (1,3), and six known compounds (7)(8)(9)(10)(11)(12) were isolated from the mycelial solid culture of an endophytic fungus P. ochrochloron SWUKD4.1850 from the medicinal plant K. angustifolia after successive separation steps using various column chromatography (CC) methods (▶ Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…1). The known compounds were identified as aigialomycin F (7) [3], aigialomycin A (8) [18], aigialomycin B (9) [18], aigialomycin D (10) [18], zeaenol (11) [19], and oxozeaenol (12) [20] by comparison of their spectroscopic data with those reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Cobimetinib is a MEK inhibitor, recently approved by the FDA for treatment of patients with B-Raf V600E mutation-positive melanoma in combination with vemurafenib (Garnock-Jones, 2015 ). Hypothemycin is a resorcylic acid lactone that has been reported to selectively and irreversibly inhibit protein kinases that contain a conserved cysteine residue (Cys 166 ) in the ATP-binding site, including the mitogen-activated protein kinase (MEK) and the extracellular signal-regulated kinase (ERK) (Fukazawa et al, 2010 ). These CellMiner TM results suggested that the new MEA analogs might impact signal transduction through the ERK cascade.…”
Section: Resultsmentioning
confidence: 99%
“…Hypothemycin ( 16 ), a resorcylic acid lactone polyketide isolated from a fungal culture Setophoma terrestris (MSX45109), could inactivate protein kinases by binding to a cysteine conserved in 46 protein kinases, including MEK, extracellular signal‐regulated kinase (ERK), and platelet‐derived growth factor receptor (PDGFR). [ 51–53 ] Hypothemycin (IC 50 : 0.58 and 2.14 µM, MTT assay) showed promising activity against MDA‐MB‐435 and SW‐620 cancer cell lines, demonstrating its potential for the development of novel anti‐breast cancer agents. [ 54 ]…”
Section: ‐Membered Macrolactonesmentioning
confidence: 99%